CARACTERIZACION DE ARCILLAS DE LA PROVINCIA DE MORROPON POR TECNICAS FISICAS Y QUIMICAS - Quille R., Rubén (2006)
The ceramic industry is the most important activity of Chulucanas, capital of the Province of Morropón, and La Encantada District. Both districts belong to the department of Piura, where there is a great demand of clay as raw material for the ceramic paste elaboration. Traditionally have existed evidences of important clay deposits but they have not yet completely characterized. That is way, considering the importance of this raw material for the ceramic industry of the region and the difficulties to get cheap commercial ceramic material of quality; we show the results of the characterization by physics and chemistry techniques of clays extracted from the zone.